Uma investigação dos aspectos fisiológicos, didáticos, estéticos e interpretativos da Messa di Voce - Diego de Almeida Pereira (2014)
This study sought to investigate the physiological, didactic, aesthetic, and interpretative implications of the messa di voce (MDV) when it is used by singers. I noticed that the attainment of the MDV requires a flawless control of the anatomical structures which participates in the vocal production, since its standard dynamical variation (a crescendo followed by a diminuendo done on the same frequency) encompasses good pneumophonic coordination, good control of the airs exit from the expiration, and vocal stability to sustain the refinement quality of the voice. I observed, thus, the efficiency of the MDV in the training and vocal improvement of erudite singers, which already came to light by many professors and singing theorists from past times who whistled it with the very ideal of vocal emission of the well-singing art. Many old singing treatises gave orientations about the MDVs performance and correlated it with other vocal technical aspects as vocal registers, mouths posture and the voices timbre. I deepened on the MDVs aesthetical aspect, highlighting it as a musical articulation or an important ornament usually used in baroque music, enabling the interpreter different ideas from the musical context, stressing the technical potentialities and the singers virtuosity. Furthermore, I explored the many names that MDV has received throughout the centuries according to his function and geographical location and that today it is mainly used in the Italian language. Another discovery was that above the different positions in respect to its terminology and its meaning, MDV possesses an intrinsic relationship with the practice of good use and refinement of the voice. From this art, one perceives the singings didactic function as well as his own possibilities in music practice. Through musical analysis of the Baroque period, based on the aesthetical inquiring previously done, this study went after helping other interprets to perform pieces that suggest the use of the MDV and to emphasize the importance of such researches to realize choices of interpretation.